X-Ray Reflection from Inhomogeneous Accretion Disks. II. Emission-Line Variability and Implications for Reverberation Mapping - Ballantyne, D. R; Turner, N. J; Young, A. J (The Astrophysical journal, 2005)
One of the principal scientific objectives of the upcoming Constellation-X mission is to attempt to map the inner regions of accretion disks around black holes in Seyfert galaxies by reverberation mapping of the Fe K alpha fluorescence line. This area of the disk is likely to be radiation pressure dominated and subject to various dynamical instabilities. Here, we show that density inhomogeneities in the disk atmosphere resulting from the photon bubble instability (PBI) can cause rapid changes in the X-ray reflection features, even when the illuminating flux is constant. Using a simulation of the development of the PBI, we find that for the disk parameters chosen, the Fe K alpha and O VIII Ly alpha lines vary on timescales as short as a few hundredths of an orbital period. In response to the changes in accretion disk structure, the Fe K alpha equivalent width (EW) shows variations as large as similar to 100 eV. The magnitude and direction (positive or negative) of the changes depends on the ionization state of the atmosphere. The largest changes are found when the disk is moderately ionized. The O VIII EW varies by tens of eV and exhibits plenty of rapid, low-amplitude changes. This effect provides a natural explanation for some observed instances of short-timescale Fe K alpha variability that was uncorrelated with the continuum (e.g., Mrk 841). New predictions for Fe K alpha reverberation mapping should be made that include the effects of this accretion disk-driven line variability and a variable ionization state. Reflection spectra averaged over the evolution of the instability are well fitted by constant-density models in the 2-10 keV region.